2013
DOI: 10.1097/anc.0b013e31827ece0a
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Necrotizing Enterocolitis With Standardized Feeding Protocols

Abstract: cell transfusions, 6 formula feeding, 7 and admission to NICUs with high endemic NEC rates, 8,9 implying that at least some of the risk factors for NEC are modifiable. 10-13 Indeed, in a compelling article, "Can We Cut the Incidence of Necrotizing Enterocolitis in Half-Today?" Dr Robert Christensen argued that adopting 2 practices-near-exclusive human milk feeding and the use of standardized feeding protocols (SFPs)-could do just that, yet clinicians must possess the will to do so. 14 In a Cochrane systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Other studies have highlighted the importance of standardized feeding protocols LGA ¼ large-for-gestational age; NEC ¼ necrotizing enterocolitis; OR ¼ odds ratio; SGA ¼ small-for-gestational age; VLBW ¼ very-low-birth-weight. as strategies for achieving full enteral feeding and, therefore, preventing NEC (24).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have highlighted the importance of standardized feeding protocols LGA ¼ large-for-gestational age; NEC ¼ necrotizing enterocolitis; OR ¼ odds ratio; SGA ¼ small-for-gestational age; VLBW ¼ very-low-birth-weight. as strategies for achieving full enteral feeding and, therefore, preventing NEC (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past 2 decades several studies have suggested that using minimal enteral nutrition, which involves providing small quantities of feeding, initially usually less than 20 ml/kg/day for the first couple of days and then advancing to 20-35 ml/kg/day, appears to be relatively safe [61,62]. Several neonatal intensive care units have instituted nutritional and feeding guidelines [63,64], and these have been successfully utilized and actually have been shown to be efficacious in the prevention of NEC [65]. …”
Section: Preventative Measuresmentioning
confidence: 99%
“…32 The risk of distension in premature and sick infants needs to be addressed in the creation of "standardized feeding" protocols and practices, not just as a sign of potential intolerance but as a risk of BT and subsequent systemic infection. 33 In January 2013, the National Healthcare Safety Network introduced a modified definition for laboratoryconfirmed bloodstream infection (BSI). 34 The definition provides a mechanism to designate a BSI as related to mucosal barrier injury (MBI), but this pathogenesis is less well defined and understood in the neonatal population.…”
Section: Gastrointestinal Tract and Enteral Feedingmentioning
confidence: 99%